KOMUNIKAI ANTARPERSONAL ANTARA PELATIH DAN ATLIT KARATE DOJO INKAI CIKO (CIREBON KOTA) - Farras, Muhammad Farras Firmansyah; Yahya Iqbal Hamidy; Yusuf Alfiansyah; Farida Nurfalah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
Communication is one of the components that support the success of training. The method used in this study is a qualitative descriptive method, which gives an overview of a situation that is taking place at the time of the research carried out and examines the cause of a particular symptom. The data collection techniques in this study are interviews as well as library studies. The results of the data collection are then presented qualitatively and descriptively, with reference to the Theory of Interpersonal Communication Effectiveness. From this study, it is known that the interpersonal communication carried out by coaches and athletes in Dojo Inkai Cirebon to improve performance so far has gone well, by having done various forms of communication in both verbal and non-verbal. The obstacles that can occur in this communication process are human and psychological factors